Powerful change part 2: Reducing the power demands of mobile devices - BALAN, Rajesh Krishna (Institutional Knowledge at Singapore Management University, 2004)
Consumers expect their mobile devices to be small and light, have a decent battery lifetime, and still be powerful enough to run all their desired applications. The need to satisfy such consumer demands has driven mobile-device manufacturers to make products (such as PDAs and cell phones) that match these needs. However, this inevitably requires tradeoffs. Building smaller, lighter devices requires sacrificing the device's battery capacity because battery technology is still fairly dense and heavy, and contributes most of a mobile device's size and weight. But, mobile devices with the required resources to run useful desktop applications need additional battery power to run those resources for a reasonable length of time. Because the tension facing manufacturers appears to be in deciding the battery-weight and battery-performance tradeoffs, the solution seems to lie in finding ways to increase a mobile device's battery lifetime.